A minimal non-radiative recombination loss for efficient non-fullerene all-small-molecule organic solar cells with a low energy loss of 0.54 eV and high open-circuit voltage of 1.15 V. Issue 28 (4th July 2018) - Yang, Daobin; Wang, Yuming; Sano, Takeshi; Gao, Feng; Sasabe, Hisahiro; Kido, Junji
Abstract : A minimal non-radiative recombination energy loss of 0.21 eV is achieved for non-fullerene all-small-molecule organic solar cells. Abstract : Organic solar cells (OSCs) are considered as a promising next-generation photovoltaic technology because of their light weight, flexibility, and the potential of roll-to-roll fabrication. However, the relatively large energy loss ( E loss ) from the optical bandgap ( E g ) of the absorber to the open-circuit voltage ( V oc ) of the device hinders further improvement of the PCEs of OSCs. Here, we report efficient non-fullerene all-small-molecule organic solar cells (NF all-SMOSCs), using DR3TBDTT and O-IDTBR as the donor and acceptor, respectively. We obtain a high electroluminescence yield (EQEEL ) value of up to ∼4 × 10 −4 corresponding to a 0.21 eV non-radiative recombination loss, which is the smallest value for bulk-heterojunction (BHJ) OSCs so far. As a result, a low E loss of 0.54 eV and a considerably high V oc of 1.15 V are obtained for BHJ NF all-SMOSCs.